Supply chain sustainability performance indicators-A systematic literature review - Muhammad Amad Saeed; Wolfgang Kersten (Logistics Research, 2020)
This research article aims to identify sustainability performance indicators (SPIs) and provide practical guidance for assessing organizations and their supply chains' sustainability-related performances. We conducted a systematic literature review to analyze scientific journal articles related to sustainable supply chains and performance measurement. We assessed sustainability performance by identifying 1054 indicators from selected scientific journal articles. In addition, in-depth analyses of selected journal articles, predefined attribute categories, and the text restructuring resulted in a unique and coherent list of 68 SPIs. Of these SPIs, 47% originated from the environmental sustainability dimension, 31% from the social sustainability dimension, and 22% from the economic sustainability dimension. The systematic literature review's results identified a complete lack of agreement on how to measure organizations and their supply chains' sustainability performances.
urn:nbn:de:gbv:830-882.0120972; hdl:11420/8449
Keywords: 650; sustainable supply chain management; systematic literature review; sustainability; performance measurement; key performance indicators